2019
DOI: 10.11646/phytotaxa.414.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The genus Marasmius (Basidiomycota, Agaricales, Marasmiaceae) from Republic of São Tomé and Príncipe, West Africa

Abstract: This treatise serves as a preliminary monograph and phylogenetic treatment of Marasmius from the African island nation of São Tomé and Príncipe (ST&P), based on data generated from 30 specimens collected in 2008. Twenty-one species are described, seven of which represent species new to science (Marasmius albisubiculosus, M. diversus, M. elaeocephaliformis, M. laranja, M. leptocephalus, M. paratrichotus, M. segregatus), and all represent new distribution records for ST&P. Species are delimited based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Distribution — Originally described from Thailand ( Wannathes et al 2009 ) and also found in Príncipe ( Grace et al 2019 ), it is herein recorded for the first time from Brazil.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Distribution — Originally described from Thailand ( Wannathes et al 2009 ) and also found in Príncipe ( Grace et al 2019 ), it is herein recorded for the first time from Brazil.…”
Section: Resultsmentioning
confidence: 77%
“…1b–c, e , 2 ), showing multiple emergence considering the traditional sectional pattern (only Globulares -type cells in the pileipellis) across the entire section that is also in agreement with previous studies ( Tan et al 2009 , Wannathes et al 2009 ). Unfortunately, the data published by Shay et al (2017) and Grace et al (2019) were not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Background. Marasmius paratrichotus was described from the west African island nation of São Tomé and Príncipe (ST&P) by Grace et al (2019). It forms a sister clade to M. trichotus (Figure 2) described from Singapore by Corner (1996).…”
Section: Resultsmentioning
confidence: 99%
“…However, the remoteness of its tropical distribution means little survey effort has been made in other likely habitats. The addition of two collections (GenBank ON715786 & OQ725928) that are >99% similar to the ST&P collection, (GenBank KX953749 Grace et al 2019), in the nrITS region is important in confirming the validity of the species as distinct from M. trichotus. Marasmius paratrichotus is morphologically similar to M. trichotus, which has an Asian and Oceania distribution including Thailand (Wannathes et al 2009) and Papua New Guinea (Desjardin & Horak 1997).…”
Section: Marasmius Paratrichotusmentioning
confidence: 99%
See 1 more Smart Citation